DEXi Suite: DEXi decision modelling software - Marko Bohanec (SoftwareX, 2025)
DEX (Decision EXpert) is a qualitative multi-criteria decision modelling method, and DEXi is software that supports the development of DEX models and their use for the evaluation and analysis of decision alternatives. We present DEXi Suite, a new generation of DEXi software, aimed at replacing the reliable and trusted, but dated, DEXi Classic software. DEXi Suite has been designed to employ a more modern and flexible software architecture and support extended functionality, while still remaining user-friendly and free to use. Currently, DEXi Suite consists of a DEXi modelling class library (DEXiLibrary), interactive desktop model editing and decision analysis software (DEXiWin) and a command-line evaluator (DEXiEval).